MENINGKATKAN KOMPETENSI PEDAGOGIK UNTUK INOVASI GURU PAUD - Joseph, Lourine Sience; Salenussa, Diane (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Abstract : Research on improving pedagogical for innovation in the teaching quality of PAUD teachers needs to be examined critically in the framework of complementing previous studies whose study tends to focus on normative facts rather than empirical social facts. In line with that, this paper aims to find out how to “Improve Pedagogic Comptence for Innovation in the Teaching Quality of PAUD Teachers. This research is a type of qualitative research with data collection techniques in the form of distributing instruments and interviews with instrumen being a list of written questions given to informants. Data from interviews and distribution of instruments aims to determine the pedagogical competence of PAUD teachers for teaching innovation for students. Through interview guidelines and the distribution of instruments given to 16 informants, they were analyzed using qualitative descriptive analysis techniques and obtained research results which showed that of the 16 PAUD teachers, the majority did not properly understand pedagogical competencies for teaching innovation. So it can be concluded, there has been an increase in the pedagogical competence of PAUD teachers after strategic were carried out by researchers. Teachers form each school experienced improvements both from the ability to understand the characteristic of students using a number of indictors to the ability to develop them in the process of educating and teaching. Keywords: Pedagogical Competence, Teaching Innovation, PAUD Teacher